The neuropathological basis of elevated serum neurofilament light following experimental concussion - John D. Arena; Douglas H. Smith; Ramon Diaz Arrastia; D. Kacy Cullen; Rui Xiao; Jiaxin Fan; Danielle C. Harris; Cillian E. Lynch; Victoria E. Johnson (Acta Neuropathologica Communications)
Abstract Mild traumatic brain injury (mTBI) or concussion is a substantial health problem globally, with up to 15% of patients experiencing persisting symptoms that can significantly impact quality of life. Currently, the diagnosis of mTBI relies on clinical presentation with ancillary neuroimaging to exclude more severe forms of injury. However, identifying patients at risk for a poor outcome or protracted recovery is challenging, in part due to the lack of early objective tests that reflect the relevant underlying pathology. While the pathophysiology of mTBI is poorly understood, axonal damage caused by rotational forces is now recognized as an important consequence of injury. Moreover, serum measurement of the neurofilament light (NfL) protein has emerged as a potentially promising biomarker of injury. Understanding the pathological processes that determine serum NfL dynamics over time, and the ability of NfL to reflect underlying pathology will be critical for future clinical research aimed at reducing the burden of disability after mild TBI. Using a gyrencephalic model of head rotational acceleration scaled to human concussion, we demonstrate significant elevations in serum NfL, with a peak at 3 days post-injury. Moreover, increased serum NfL was detectable out to 2 weeks post-injury, with some evidence it follows a biphasic course. Subsequent quantitative histological examinations demonstrate that axonal pathology, including in the absence of neuronal somatic degeneration, was the likely source of elevated serum NfL. However, the extent of axonal pathology quantified via multiple markers did not correlate strongly with the extent of serum NfL. Interestingly, the extent of blood–brain barrier (BBB) permeability offered more robust correlations with serum NfL measured at multiple time points, suggesting BBB disruption is an important determinant of serum biomarker dynamics after mTBI. These data provide novel insights to the temporal course and pathological basis of serum NfL measurements that inform its utility as a biomarker in mTBI.